(untitled) (Global Journal of Human-Social Science, 2020)
Malaysian healthcare is nominated as one of the best healthcare providers in the world However does this fact reflect the patients satisfaction Therefore this research aims to investigate whether empathy competency and service quality influence patients satisfaction in healthcare services in Selangor Malaysia Primary data are collected using a selfadministered questionnaire and a sample of 206 patients from four government and private hospitals in Selangor Data were analysed through descriptive statistics correlation and regression analysis The findings show that empathy has the strongest relationship 403 followed by service quality with 284 and competency 176 All factors also influenced patients satisfaction All identified variables contribute to a big amountof variances R2 66 8percent to the overall hospital performance that makes its client happy and satisfied The understanding patients satisfaction will lead to many improved services Practically this study can contribute to a better experience for patients and knowledge for hospitals to strive for a better service healthcare provider